New Combinations in Combretaceae subtribe Combretinae from Africa and Asia - Maurin, Olivier; Turner, Ian M.; Boatwright, James S.; Christenhusz, Maarten J.m. (Phytotaxa, 2020)
Recent molecular evidence has confirmed that Meiostemon and Quisqualis are embedded in Combretum. While some of the species in the two former genera have already been transferred to Combretum, several combinations are still wanting. New combinations for these species in Combretum are therefore formalised here for taxa of Meiostemon and Quisqualis that had not been formally transferred yet. Additionally, we list recently described taxa that are placed in Combretum subgenus Cacoucia section Quisqualis.